Pengaruh karakteristik generasi alpha terhadap efektivitas implementasi Pendidikan Agama Islam di SMP Muhammadiyah 3 Yogyakarta - Aulia, Muhammad Faizul; Makrufi, Anisa Dwi (TAWAZUN: Jurnal Pendidikan Islam, 2025)
The rapid development of technology has a major influence on the characteristics of Generation Alpha, which was born and grew up in the digital era. This generation has a different learning style compared to previous generations, which impacts the effectiveness of implementing Islamic Religious Education at school. This study aims to analyze the influence of Generation Alpha characteristics on the effectiveness of the implementation of Islamic Religious Education at SMP Muhammadiyah 3 Yogyakarta. The research method used is a quantitative approach with a survey using a questionnaire as the main instrument and interviews as an additional instrument. Data were collected through questionnaires given to 100 7th-grade students as a representation of Generation Alpha. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method to examine the relationship between the characteristics of Generation Alpha and the effectiveness of Islamic Religious Education implementation. The results showed that the characteristics of Generation Alpha, which are closely related to digital technology, positively influence the effectiveness of the implementation of Islamic Religious Education. Students understand the material more easily when delivered with interactive digital-based learning methods. Teachers also adapt to technology in learning to increase student engagement. Nonetheless, challenges in maintaining student focus remain, especially in optimizing the use of technology to remain relevant to the objectives of religious education. Implementing digital-based learning methods can increase the effectiveness of Islamic Religious Education for Generation Alpha. Therefore, there is a need for continuous innovation in teaching methods to suit this generation's characteristics and instill religious values optimally. Abstrak Perkembangan teknologi yang pesat membawa pengaruh besar terhadap karakteristik Generasi Alpha yang lahir dan tumbuh dalam era digital. Generasi ini memiliki gaya belajar yang berbeda dibandingkan generasi sebelumnya, yang berdampak pada efektivitas implementasi Pendidikan Agama Islam di sekolah. Penelitian ini bertujuan untuk menganalisis pengaruh karakteristik Generasi Alpha terhadap efektivitas implementasi Pendidikan Agama Islam di SMP Muhammadiyah 3 Yogyakarta. Metode penelitian yang digunakan adalah pendekatan kuantitatif dengan survei menggunakan kuesioner sebagai instrumen utama serta wawancara sebagai instrumen tambahan. Data dikumpulkan melalui kuesioner yang diberikan kepada 100 siswa kelas 7 sebagai representasi Generasi Alpha. Analisis data dilakukan menggunakan metode Partial Least Squares-Structural Equation Modeling (PLS-SEM) untuk menguji hubungan antara karakteristik Generasi Alpha dan efektivitas implementasi Pendidikan Agama Islam. Hasil penelitian menunjukkan bahwa karakteristik Generasi Alpha yang erat dengan teknologi digital berpengaruh positif terhadap efektivitas implementasi Pendidikan Agama Islam. Siswa lebih mudah memahami materi ketika disampaikan dengan metode pembelajaran berbasis digital yang interaktif. Guru juga beradaptasi dengan penggunaan teknologi dalam pembelajaran untuk meningkatkan keterlibatan siswa. Meskipun demikian, tantangan dalam menjaga fokus siswa tetap ada, terutama dalam mengoptimalkan penggunaan teknologi agar tetap relevan dengan tujuan pendidikan agama. Penerapan metode pembelajaran berbasis digital dapat meningkatkan efektivitas Pendidikan Agama Islam bagi Generasi Alpha. Oleh karena itu, perlu adanya inovasi berkelanjutan dalam metode pengajaran agar sesuai dengan karakteristik generasi ini dan mampu menanamkan nilai-nilai agama secara optimal.